Carbon abatement with renewables: evaluating wind and solar subsidies in Germany and Spain - Abrell, Jan; Kosch, Mirjam; Rausch, Sebastian (Journal of public economics, 2019)
This paper exploits the exogeneity of weather conditions to evaluate renewable energy (RE) subsidies in Germany and Spain in terms of their short-run direct program costs for reducing carbon dioxide emissions. We find that both aggregate costs and their distribution between energy producers and consumers vary significantly depending on which type of RE technology is promoted — reflecting substantial heterogeneity in production costs, temporal availability of natural resources, and market conditions, i.e., time-varying demand, carbon intensity of installed production capacities, and opportunities for cross-border trade. We estimate that the costs for reducing 1ton of CO2 through subsidies for solar are 411 to 1944€. Subsidizing wind entails significantly lower costs, ranging from 82 to276€. In the short run, the economic rents for energy producers always decrease, while consumers incur four to seven times larger costs when solar is promoted but gain under RE policies promoting wind.